Bragg gratings in imprinted Ormocer® waveguides - Girschikofsky, Maiko Girschikofsky; Förthner, Michael; Rommel, Matthias; Frey, Lothar; Hellmann, Ralf (24th International Conference on Plastic Optical Fibers, POF 2015, 2015)
Volume-type Bragg gratings have been fabricated within planar rib-type waveguides based on the inorganic- organic hybrid polymer OrmoComp®. The waveguides have been achieved using the innovative UV enhanced substrate conformal imprint lithography, which allows for a large area patterning at high throughput. For the inscription of volume-type Bragg gratings, the static phase-mask technique was applied with a KrF excimer laser as light source. By applying this technique, well defined Bragg gratings have been achieved within pre-cured OrmoComp® featuring a high reflectivity of up to 80 % and a small full width at half maximum of down to 130 pm. The fabricated volume-type Bragg grating was furthermore applied in the field of temperature sensing, where a high sensitivity of -130 pm/°C was found, which corresponds to a limit of detection of only 4.6 10-2 °C.
Keywords: Bragg gratings; Hybrid polymer; Imprint lithography; Planar waveguides; Temperature sensing

Combination of direct laser writing and soft lithography molds for combined nano- and microfabrication - Rumler, Maximilian; Kollmuss, M.; Baier, L.; Michel, F.; Förthner, Michael; Becker, M.; Rommel, Mathias; Frey, Lothar (SPIE-INT SOC OPTICAL ENGINEERING, PO BOX 10, BELLINGHAM, WA 98227-0010 USA, 2016)
This work presents a novel approach for combined micro- and nanofabrication based on the local laser exposure of an UV-curing material through a structured mold. The proposed process makes use of the high freedom of design of direct laser writing (DLW) and the high resolution of soft lithography molds (made e.g. from PDMS). By optimizing the exposure process it was possible to fabricate locally defined hierarchical structures with a height of around 16 um, that are fully covered with nanometer-sized holes using OrmoComp (R). Manual test imprints showed that the fabricated structures can be used for "step & repeat" nanoimprint processes. Furthermore, the local transfer of nanostructures into two different soft lithography resists (Katiobond 110707, mr-NIL210) was investigated. Diffusion of resist components into the PDMS mold was observed and could be prohibited by the use of hybrid molds, which employ OrmoComp as structure containing layer. First experiments revealed successful transfer of the mold's nanostructures into mr-NIL210 but still leave room for improvement concerning the process parameters.
Keywords: direct laser writing; nanoimprint lithography; soft lithography; hierarchical structures; hybrid polymer; PDMS

Fabrication of Bragg grating sensors in UV-NIL structured Ormocer waveguides - Girschikofsky, Maiko Girschikofsky; Förthner, Michael; Rommel, Matthias; Frey, Lothar; Hellmann, Ralf (Integrated Optics: Devices, Materials, and Technologies XXI 2017, 2017)
We report on the fabrication and characterization of Bragg gratings in UV-NIL structured Ormocer hybrid polymer rib-type waveguides using phase mask technology. The inuence of fabrication parameters such as the applied laser uence during the inscription process and the grating's length on the spectral behavior of the waveguide Bragg gratings was experimentally determined and compared to numerical simulations and calculations. To investigate potential sensor applications, the sensitivity of the thus fabricated optical devices towards refractive index changes of the gratings' surrounding (qualification for bio-and chemical sensing) as well as the sensitivity towards temperature and relative humidity were determined. © 2017 SPIE.
Keywords: Bragg grating; Hybrid polymer; Nanoimprint lithography; Ormocer; Sensor

Flexible thin film bending sensor based on Bragg gratings in hybrid polymers - Girschikofsky, Maiko Girschikofsky; Rosenberger, Manuel; Förthner, Michael; Rommel, Matthias; Frey, Lothar; Hellmann, Ralf (Optical Sensing and Detection V 2018, 2018)
Keywords: Bragg Grating; Hybrid Polymer; Bending Sensor; Ormocer; Thin Film

Hybrid polymers processed by substrate conformal imprint lithography for the fabrication of planar Bragg gratings - Förthner, Michael; Rumler, Maximilian; Stumpf, F.; Fader, R.; Rommel, Mathias; Frey, Lothar; Girschikofsky, M.; Belle, S.; Hellmann, R.; Klein, J. J. (Applied Physics A-Materials Science & Processing, 2016)
In this work, we present an approach to use UV-enhanced substrate conformal imprint lithography (UV-SCIL) as a soft imprint technique combined with excimer laser irradiation to manufacture Bragg gratings within planar waveguides on a full-wafer scale. For the first time, different hybrid polymers (OrmoComp (R), OrmoStamp, OrmoCore, OrmoClad and OrmoClear) could be successfully patterned using UV-SCIL. For OrmoComp (R) (showing results very similar to OrmoStamp and OrmoClad), a complete imprint process could be realized. OrmoCore formed an inhibition layer in the presence of oxygen during the imprint, as could be observed for the use of OrmoClear as well. Processing options were elaborated to reduce the inhibition effect significantly, whereby the latter is mainly due to the atmospheric oxygen-containing PDMS layer of the UV-SCIL working stamp. Further on, the successful realization of a planar Bragg grating operating at the telecom wavelength is demonstrated by tuning the refractive index (RI) of OrmoComp (R) using a phase mask and an UV excimer laser. FTIR measurements show that the change in RI can be clearly correlated with a change in the chemical composition of the hybrid polymer during laser exposure.

One-step nanoimprinted Bragg grating sensor based on hybrid polymers - Förthner, Michael; Girschikofsky, M.; Rumler, Maximilian; Stumpf, F.; Rommel, Mathias; Hellmann, R.; Frey, Lothar (Sensors and Actuators A-Physical, 2018)
Keywords: Bragg grating; Nanoimprint; Temperature sensor; Refractive index sensing; SCIL

Polymerization related deformations in multilayer soft stamps for nanoimprint - Förthner, Michael; Papenheim, Marc; Rumler, Maximilian; Stumpf, Florian; Baier, Leander; Rommel, Matthias; Scheer, Hella Christin; Frey, Lothar (Journal of Applied Physics, 2017)
This paper presents a study concerning the macroscale deformation of soft stamps for nanoimprint lithography. Composite stamps consisting of two or three layers were prepared with varying process parameters, and the bow of the stamps was investigated with an optical profilometer. Deflection measurements were compared with results from a mechanical model in order to prove its validity. The composite stamps were prepared from polydimethylsiloxane (S-PDMS) and OrmoStamp® layers on different substrate materials (silicon or AF-32-glass). The influence of selected preparation parameters on the deformation was investigated, such as layer thickness, curing, and hardbake temperatures, as well as UV-exposure intensities. It is discussed how an appropriate choice of preparation parameters can reduce the deformation, too. By decreasing the curing intensity of a thin OrmoStamp layer, coated on top of a silicon wafer, from 200 mW/cm2 to 2 mW/cm2, the deformation was reduced from 6 μm to 0. It is shown that the mechanical model is capable of predicting the deformation of composite stamps consisting of OrmoStamp layers on top of a silicon substrate. Further on, deformation results for S-PDMS top layers are presented and discussed. As a promising process option for the reduction of stamp deformations, a new, room temperature curable PDMS recipe is introduced. For composite stamps prepared with this material, the deformation value was reduced below 10 μm, compared to values ranging from 10 μm up to 127 μm for thermally cured S-PDMS (50 °C or 70 °C). Finally, different two-layer stamps were coated with an additional third layer and measured again, in order to investigate the deflection for tri-layered cases. The research is of high relevance for the fabrication and application of substrate conformal imprint lithography stamps with minimized deflection. © 2017 Author(s).

TiO2 surface functionalization of COC based planar waveguide Bragg gratings for refractive index sensing - Rosenberger, Manuel; Girschikofsky, M.; Förthner, Michael; Belle, S.; Rommel, Mathias; Frey, Lothar; Schmauß, Bernhard; Hellmann, R. (Journal of Optics, 2018)
We demonstrate the applicability of a planar waveguide Bragg grating in cyclo-olefin copolymer (COC) for refractive index sensing. The polymer planar waveguide Bragg grating fabricated using a single writing step technique is coated with a high-index layer of titanium dioxide (TiO2) leading to a distinct birefringence. This in turn results in the splitting of the Bragg reflection into two distinct Bragg wavelengths, which strongly differ regarding their refractive index sensitivities. Where one wavelength is only slightly affected by the ambient refractive index, the second Bragg peak shows a strong sensitivity. Furthermore, we investigate the temperature behaviour of the functionalized sensor and discuss it with respect to applications in refractive index sensin
Keywords: Bragg grating; high index layer; integrated waveguide; polymer optics; refractive index sensing

Waveguide Bragg gratings in Ormocer hybrid polymers - Frey, Lothar; Förthner, Michael; Hellmann, Ralf; Rommel, Matthias; Girschikofsky, Maiko Girschikofsky (Optics Express, 2016)
We report on the fabrication of Bragg gratings within rib-type waveguides of previously UV-cured inorganic-organic Ormocer hybrid polymers by applying the interferometric phase mask technique in conjunction with deep-UV laser radiation. The fabrication process as well as the influence of the applied laser fluence and the length of the Bragg grating on the characteristics of the Bragg grating's transmission and reflection spectra are discussed and compared to numerical simulations and calculations. Depending on the applied laser fluence and the chosen grating length, waveguide Bragg gratings with strong reflectivities of up to 98% and narrow bandwidths of down to 120 pm have been achieved. (C) 2016 Optical Society of America

Waveguide Bragg Gratings in Ormocer®s for Temperature Sensing - Girschikofsky, Maiko Girschikofsky; Rosenberger, Manuel; Förthner, Michael; Rommel, Mathias; Frey, Lothar; Hellmann, Ralf (Sensors, 2017)
Embedded channel waveguide Bragg gratings are fabricated in the Ormocer® hybrid polymers OrmoComp®, OrmoCore, and OrmoClad by employing a single writing step technique based on phase mask technology and KrF excimer laser irradiation. All waveguide Bragg gratings exhibit well-defined reflection peaks within the telecom wavelengths range with peak heights of up to 35 dB and –3 dB-bandwidths of down to 95 pm. Furthermore, the dependency of the fabricated embedded channel waveguide Bragg gratings on changes of the temperature and relative humidity are investigated. Here, we found that the Bragg grating in OrmoComp® is significantly influenced by humidity variations, while the Bragg gratings in OrmoCore and OrmoClad exhibit linear and considerably high temperature sensitivities of up to –250pm/°C and a linear dependency on the relative humidity in the range of –9 pm/%. © 2017 by the authors. Licensee MDPI, Basel, Switzerlan
Keywords: Bragg grating; Humidity; Hybrid polymer; Ormocer®; Temperature